Voices of Chinese international students in USA colleges: 'I want to tell them that … '. Issue 5 (4th May 2017) - Heng, Tang T.
Abstract : As international student mobility worldwide reach new heights, there have been increasing conversations around how tertiary institutions need to rethink how they relate to and support international students for success. This study asks mainland Chinese students, the largest proportion of international students worldwide, to voice their desires about how their USA institutional communities can support their college experience. Through 3 interviews and 4 journals with 18 first and second year students, it was found that Chinese internationals wanted their professors and host peers to be cognizant of and curious about their backgrounds, as well as to show care and initiative in approaching them. They also asked for improved international student services and more academic support to decode implicit norms of the academy. Findings stress the imperative for institutions to include international students in voicing ways to enhance their college experience so that all institutional members can benefit from the internationalization of higher education.